Estimating coverage of a women's group intervention among a population of pregnant women in rural Bangladesh - Younes Layla; Houweling Tanja AJ; Azad Kishwar; Costello Anthony; Fottrell Edward (BMC, 2012)
Abstract Background Reducing maternal and child mortality requires focused attention on better access, utilisation and coverage of good quality health services and interventions aimed at improving maternal and newborn health among target populations, in particular, pregnant women. Intervention coverage in resource and data poor settings is rarely documented. This paper describes four different methods, and their underlying assumptions, to estimate coverage of a community mobilisation women's group intervention for maternal and newborn health among a population of pregnant women in rural Bangladesh. Methods Primary and secondary data sources were used to estimate the intervention's coverage among pregnant women. Four methods were used: (1) direct measurement of a proxy indicator using intervention survey data; (2) direct measurement among intervention participants and modelled extrapolation based on routine longitudinal surveillance of births; (3) direct measurement among participants and modelled extrapolation based on cross-sectional measurements and national data; and (4) direct measurement among participants and modelled extrapolation based on published national data. Results The estimated women's group intervention's coverage among pregnant women ranged from 30% to 34%, depending on method used. Differences likely reflect differing assumptions and methodological biases of the various methods. Conclusion In the absence of complete and timely population data, choice of coverage estimation method must be based on the strengths and limitations of available methods, capacity and resources for measurement and the ultimate end user needs. Each of the methods presented and discussed here is likely to provide a useful understanding of intervention coverage at a single point in time and Methods 1 and 2 may also provide more reliable estimates of coverage trends. Footnotes 1Unpublished data from three focus group discussions with women's group members and facilitators participating in the Women's Groups intervention.